Death drive in the first Ferenczi: a quiet state, regression, and the beginnings of psychic life: a quiet state, regression, and the beginnings of psychic life - Dal Molin, Eugênio Canesin; Coelho Junior, Nelson Ernesto; Cromberg, Renata Udler (Clinical Styles. The Journal on the vicissitudes of childhood, 2019)
This article seeks to present and discuss Ferenczi's use of the idea of a death drive in the 1910s. We present the history and context of the use of the idea among the first psychoanalysts, and then argue that Ferenczi's first hypothesis on the death instinct sought to relate a stage of unconditional omnipotence, characteristic, in his view, of intrauterine life, with an original state of quietness, a tendency to regression and a conception of primitive narcissism. We then compare each one of these aspects with the Freudian theory. In conclusion, we make a critical analysis of the hypothesis using the ideas of other authors.